Care of Astronomical Telescopes and Accessories A Manual for the Astronomical Observer and Amateur Telescope Maker - Pepin, M. Barlow; SpringerLink (Online service) (London : Springer London, 2005)
Commercially-made astronomical telescopes are better and less expensive than ever before, and their optical and mechanical performance can be superb. When a good-quality telescope fails to perform as well as it might, the reason is quite probably that it needs a little care and attention! Here is a complete guide for anyone who wants to understand more than just the basics of astronomical telescopes and accessories, and how to maintain them in the peak of condition. The latest on safely adjusting, cleaning, and maintaining your equipment is combined with thoroughly updated methods from the old masters. Here, too, are details of choosing new and used optics and accessories, along with enhancements you can make to extend their versatility and useful lifetime. This book is for you. Really. Looking after an astronomical telescope isn$1 (Bt only for the experts - although there are some things that only an expert should attempt - and every serious amateur astronomer will find invaluable information here, gleaned from Barlow Pepin's many years$1 (Bexperience working with optical instruments.s
Optical Equipment -- Treasure in the Cellar -- Buying It Right: Consumer Strategies -- New Instruments -- Used Equipment -- Optical Accessories -- Care and Maintenance -- Lens Optics -- Figured Mirrors and Flats -- Optical Tube Features -- Mounts and Tripods -- Collimation and Adjustment Techniques -- Protection, Refinishing and Surface Treatments -- Storage -- Equipment Projects and Tips.
Keywords: Popular works; Observations, Astronomical; Astronomy -- Observations; Astronomy; Popular Science; Popular Science in Astronomy; Astronomy, Observations and Techniques; Electronic books